1997
DOI: 10.1073/pnas.94.17.9296
|View full text |Cite
|
Sign up to set email alerts
|

Thymocyte development is normal in CTLA-4-deficient mice

Abstract: Recent studies indicate that CTLA-4 interaction with B7 ligands transduces an inhibitory signal to T lymphocytes. Mice homozygous for a null mutation in CTLA-4 have provided the most dramatic example of the functional importance of CTLA-4 in vivo. These animals develop a fatal lymphoproliferative disorder and were reported to have an increase in CD4 ؉ and CD8؉ thymocytes and CD4 ؊ CD8؊ thymocytes, and a decrease in CD4 ؉ CD8 ؉ thymocytes. Based on these observations, it was proposed that CTLA-4 is necessary fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 53 publications
9
109
2
Order By: Relevance
“…We also investigated the TCR repertoire of thymocytes in these mice by staining with mAb specific for each Vb (Vb2-14, Vb17). Similar to the results in CTLA-4 -/-mice [7,8] there was no difference in the usage of the Vb repertoire between FL-, TR-Tg mice and normal mice (data not shown). …”
Section: Thymocyte Development In Fl-and Tr-tgsupporting
confidence: 86%
See 3 more Smart Citations
“…We also investigated the TCR repertoire of thymocytes in these mice by staining with mAb specific for each Vb (Vb2-14, Vb17). Similar to the results in CTLA-4 -/-mice [7,8] there was no difference in the usage of the Vb repertoire between FL-, TR-Tg mice and normal mice (data not shown). …”
Section: Thymocyte Development In Fl-and Tr-tgsupporting
confidence: 86%
“…Whether such small numbers of Treg in Tg mice are functional and sufficient for preventing the induction of the lymphoproliferative disorder remains to be determined. It appears to be established that CTLA-4 does not affect thymocyte differentiation [7][8][9][10]. Still, this is only based on the observation that three different TCR-Tg mice (HY-Tg, LCMV-Tg, and DO11.10 TCR-Tg mice) crossed with CTLA-4 -/-mice did not reveal any gross defect in thymic positive/negative selections [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies using CTLA-4-deficient mice showed that thymocyte development is not altered in the absence of CTLA-4 (26,27), suggesting that CTLA-4 is not involved in thymocyte development. Other studies showed that the administration of CTLA-4-neutralizing Abs inhibited negative selection in vivo (13), suggesting that CTLA-4 is necessary for negative selection.…”
mentioning
confidence: 99%